FREQUENCY OF CHILD TRAFFICKING AND FORCED LABOUR: INVESTIGATING THE PREDISPOSING FACTOR IN CHILDREN’S EDUCATION - GBENGA-AKANMU, Taiwo Oladunni; ADESOKAN, Grace Omolade (Indonesian Journal of Elementary Teachers Education, 2024)
The study determined the frequency at which children trafficking and child forced labour activities are being practiced in Osun State, and examined the vulnerability of children trafficked and exposed to forced labour in the study area. The study adopted a descriptive research design. Primary data (quantitative and qualitative) involving the use of questionnaire and in-depth interview guide are sourced. In-depth interview was held with 10 senior members of the Ministry of Women Affairs and Child Development (MWACD), Director General, Deputy/Assistant Director General and Confidential Secretary of National Agency for the Prohibition of Trafficking in Person (NAPTIP) and One Divisional Police Officer (DPO). For the quantitative data, 240 copies of semi-structured questionnaire were administered to respondents selected through convenience sampling, from 12 locations in the three senatorial districts. Three instruments were used for the study; namely Forced labour Activities Checklist (CLAC) Osun State Child Trafficking and Labour Control Regulation Questionnaire (CLCRQ) for vulnerability indicators and Detection Strata Interview Guide (DS-IG). The data collected were analysed using appropriate inferential and descriptive analysis. Findings on the frequency at which child trafficking and child forced labour activities are being practiced in Osun State revealed that The Child Acts Law has a stake in ensuring that the menace is reduced. Also, the Osun State government is making effort to bring about a drastic reduction to the issues such as awareness and time-to-time sensitization. Results on the factors predisposing children into vulnerability Osun State revealed that factors such as poverty (x ̅ =1.30), poor parenting (x ̅ =1.32), ignorance / illiteracy (x ̅ =1.35), and parental economic benefits from the act (x ̅ =1.59) frequently predispose children into vulnerability of child trafficking and forced labour in Osun State. The study concluded that child trafficking and forced labour are prevalent and frequent practices in Osun State.Keywords: Child; Trafficking; Forced Labour; Predisposing; Pre-School